Great Theorists of Central European Integration in the Czech Republic - Kolumber, David; Tauchen, Jaromír (Great Theorists of Central European Integration, 2023)
The chapter examines five prominent Czech thinkers whose works contributed to the issue of Central European integration. These key figures are discussed chronologically. First, the life and work of František Palacký (1798–1876) is presented. A politician, writer and the founder of modern Czech history, Palacký contributed significantly to the political life of the nineteenth century through the question of cooperation between the Slavic peoples of the Habsburg Monarchy; the relationship of the Czech lands to German integration; and later to the Compromise of 1867. Another important figure is the politician and Czechoslovak Prime Minister Karel Kramář (1860–1937), who based his ideas on close cooperation with Russia and developed the concept of the Slavic Empire. Although the Czechoslovak President Edvard Beneš (1884–1948) is often mentioned primarily in connection with the events of 1938 (Munich Agreement), the expulsion of Germans from Czechoslovakia and 1948 (Communist putsch), Beneš had advocated the unification of the European area as a barrier against the hardships of war. These concepts were manifested not only in the Paris Peace Conference and proposals within the League of Nations, but also in the formation of the Little Entente during the interwar period and negotiations for the Czechoslovak–Polish Confederation during the Second World War. However, Beneš’s ideas ultimately failed thanks to France’s incompetence and the expansionism of the Soviet Union, which he underestimated. Another prominent integrationist theorist was the politician and national economist Jaromír Nečas (1888–1945), who developed the United States of Europe thesis and whose efforts at a peaceful solution to the Sudeten crisis are often overlooked. Czechoslovak and Czech president, playwright, and dissident Václav Havel (1936–2011) provided a philosophical dimension to the integration issue. Havel actively sought the early integration of Eastern Europe into Western European structures and was also the main initiator of close cooperation with Hungary and Poland, understanding the Euro-Atlantic orientation of the former socialist countries as a necessity. He simultaneously pointed out the mistakes that were gaining negative assessments, especially for the European Union. This chapter presents the aforementioned thinkers’ life stories and summarises their crucial works and speeches, illustrating their contribution to Central European integration.KEYWORDS: Integration, Czech Republic, Czechoslovakia, František Palacký, Karel Kramář, Edvard Beneš, Jaromír Nečas, Václav Havel